2020
DOI: 10.33321/cdi.2020.44.36
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, Australia: Epidemiology Report 12: Reporting week ending 23:59 AEST 19 April 2020

Abstract: Confirmed cases in Australia notified up to 19 April 2020: notifications = 6,606; deaths = 69. The reduction in international travel and domestic movement, social distancing measures and public health action have likely slowed the spread of the disease. Notifications in Australia remain predominantly among people with recent overseas travel, with some locally-acquired cases being detected. Most locally-acquired cases can be linked back to a confirmed case, with a small portion unable to be epidemiologically li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
(15 reference statements)
3
5
0
Order By: Relevance
“…These values are higher than what has been previously reported in other studies from China (2%), 19 Spain (2%), 20 the US (1.7%), 6 or the UK (0.9%), 21 but in line with the WHO dashboard which reported that children (>14 years) accounted for 3.7% of all COVID-19 cases, 1 or the Australian Health Protection Agency which has reported that children/adolescents (<19 year) accounted for 4% of confirmed COVID-19 cases in Australia. 22 Asthma and obesity were the most common baseline comorbidities in children/adolescents with COVID-19; this is in keeping with disease prevalence among a general pediatric population. 23 More strikingly, we observed a high prevalence of conditions that are relatively rare in children/adolescents, including congenital malformation/s, neurodevelopmental disorders, heart disease, type 1 diabetes mellitus, cancer, and chromosomal disorder/s.…”
Section: Health Outcomessupporting
confidence: 54%
“…These values are higher than what has been previously reported in other studies from China (2%), 19 Spain (2%), 20 the US (1.7%), 6 or the UK (0.9%), 21 but in line with the WHO dashboard which reported that children (>14 years) accounted for 3.7% of all COVID-19 cases, 1 or the Australian Health Protection Agency which has reported that children/adolescents (<19 year) accounted for 4% of confirmed COVID-19 cases in Australia. 22 Asthma and obesity were the most common baseline comorbidities in children/adolescents with COVID-19; this is in keeping with disease prevalence among a general pediatric population. 23 More strikingly, we observed a high prevalence of conditions that are relatively rare in children/adolescents, including congenital malformation/s, neurodevelopmental disorders, heart disease, type 1 diabetes mellitus, cancer, and chromosomal disorder/s.…”
Section: Health Outcomessupporting
confidence: 54%
“…Thus, the mean age of CSMC patients was approximately 60 years, which is consistent with older adults being more susceptible to COVID-19. 5,21,24 Patients with higher viral loads detected by RT-PCR also correlated with a higher percentage of SARS-CoV-2 genome coverage by sequencing.…”
Section: Discussionmentioning
confidence: 88%
“…After transmission from China, our timeline for SARS-CoV-2 infection follows other reported introductions into different global populations. 5,11,14,15,[23][24][25][26] At the time of our study, the only Los Angeles SARS-CoV-2 genome deposited in GISAID was not linked to a particular model of introduction. 3 Based on these cumulative findings, we hypothesize the local Los Angeles community was likely exposed to a US West Coast SARS-CoV-2 strain, which was directly transmitted from China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are higher than what has been previously reported in other studies from China (2%) [17], Spain (2%) [18], the US (1.7%) [5], or the UK (0.9%) [19], but in line with the WHO dashboard which reported that children below the age of 14 years old accounted for 3.7% of all COVID-19 cases [1], or the Australian Health Protection Agency which has reported that children/adolescents below the age of 19 years accounted for 4% of confirmed COVID-19 cases in Australia. [20]…”
Section: Discussionmentioning
confidence: 99%